Effects of slow- v. fast-digested protein supplementation combined with mixed power training on muscle function and functional capacities in older men. Issue 9 (14th May 2021) - Dulac, M. C.; Pion, C. H.; Lemieux, F. C.; Pinheiro Carvalho, L.; El Hajj Boutros, G.; Bélanger, M.; Gaudreau, P.; Chevalier, S.; Morais, J. A.; Noirez, P.; Gouspillou, G.; Aubertin-Leheudre, M.
Abstract: Ageing leads to a progressive loss of muscle function (MF) and quality (MQ: muscle strength (MS)/lean muscle mass (LM)). Power training and protein (PROT) supplementation have been proposed as efficient interventions to improve MF and MQ. Discrepancies between results appear to be mainly related to the type and/or dose of proteins used. The present study aimed at determining whether or not mixed power training (MPT) combined with fast-digested PROT (F-PROT) leads to greater improvements in MF and MQ in elderly men than MPT combined with slow-digested PROT (S-PROT) or MPT alone. Sixty elderly men (age 69 (sd 7) years; BMI 18–30 kg/m 2 ) were randomised into three groups: (1) placebo + MPT (PLA; n 19); (2) F-PROT + MPT ( n 21) and (3) S-PROT + MPT ( n 20) completed the intervention. LM, handgrip and knee extensor MS and MQ, functional capacity, serum metabolic markers, skeletal muscle characteristics, dietary intake and total energy expenditure were measured. The interventions consisted in 12 weeks of MPT (3 times/week; 1 h/session) combined with a supplement (30 g:10 g per meal) of F-PROT (whey) or S-PROT (casein) or a placebo. No difference was observed among groups for age, BMI, number of steps and dietary intake pre- and post-intervention. All groups improved significantly their LM, lower limb MS/MQ, functional capacity, muscle characteristics and serum parameters following the MPT. Importantly, no difference between groups was observed following the MPT. Altogether, adding 30 g PROT/d to MPT, regardless of the type, does not provide additional benefits to MPT alone in older men ingesting an adequate (i.e. above RDA) amount of protein per d.